𝒩-Subalgebras in BCK/BCI-Algebras Based on Point 𝒩-Structures. (26th September 2010) - Jun, Young Bae; Kang, Min Su; Park, Chul Hwan
Abstract : The notion of 𝒩 -subalgebras of several types is introduced, and related properties are investigated. Conditions for an 𝒩 -structure to be an 𝒩 -subalgebra of type ( q, ∈ ⋁ q ) are provided, and a characterization of an 𝒩 -subalgebra of type ( ∈, ∈ ⋁ q ) is considered.